2019
DOI: 10.3889/oamjms.2019.527
|View full text |Cite
|
Sign up to set email alerts
|

Gartanin Compounds from Extract Ethanol Pericarp Mangosteen (Garcinia mangostana Linn.)

Abstract: AIM: The study aimed to isolate and identification secondary metabolite from pericarp Garcinia mangostana Linn. METHODS: The first step of this research was maceration of sample using alcohol 70% solvent. The separation and purification of compounds using Vacuum Liquid Chromatography (VLC), Radial Chromatography (RC). The purity of isolate was analyzed by thin layer chromatography (TLC) and melting point. Compounds identified using spectroscopi IR, NMR-1D (1H, 13C-NMR and DEPT) and 2-D NMR (HMQC and HMBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Isocolumbin is a natural alkaloids targeting the epidermal growth factor receptor in nonsmall cell lung cancer . Gartanin, which is first identified in the purple mangosteen fruit, is a potent growth inhibitor of various cancer cell lines. , In T. cuspidata, isocolumbin and gartanin are two vascular bundle cell specifically accumulated active compounds (>90%), suggesting their movement between plant tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isocolumbin is a natural alkaloids targeting the epidermal growth factor receptor in nonsmall cell lung cancer . Gartanin, which is first identified in the purple mangosteen fruit, is a potent growth inhibitor of various cancer cell lines. , In T. cuspidata, isocolumbin and gartanin are two vascular bundle cell specifically accumulated active compounds (>90%), suggesting their movement between plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“… 40 Gartanin, which is first identified in the purple mangosteen fruit, is a potent growth inhibitor of various cancer cell lines. 41 , 42 In T. cuspidata , isocolumbin and gartanin are two vascular bundle cell specifically accumulated active compounds (>90%), suggesting their movement between plant tissues. Procyanidin B2 is a potent natural antioxidant exhibiting multiprotective roles in response to vitrification stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…The VLC showed that the yield of each fraction is due to the chemical composition and the equilibrium of the phases (mobile and stationary) [ 33 ]. Although VLC is used to separate extracts from other plants, our study describes the yield of separated fractions for the first time [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gartanin is a xanthone derivative found in the pericarp of the mangosteen fruit and leaves of Garcinia mangostana . It exhibits various pharmacological activities, including antifungal, antioxidant, and anticancer properties against bladder and lung cancers .…”
Section: Introductionmentioning
confidence: 99%